Building a Monthly Chronology of Recessions for the State of Espírito Santo - Augusto Reis Gomes; Matheus Albergaria de Magalhães (BBR: Brazilian Business Review)
The state of Espírito Santo has short-term fluctuations in its activity level ("business cycles") that are on average twice more volatile than fluctuations occurring in Brazil. In addition, there are differences in terms of duration between cycles occurring in the state and country. Because of this, the objective of this work is to build a monthly chronology of recessions for the Espírito Santo over the period between January 1991 and March 2012. In terms of means durations it was found that over the period analyzed the Espírito Santo went through a larger number of recessions than Brazil. On the other hand, in terms of median durations, it was noted that recessions tend to last less in the state than in the country, despite its greater relat ive volatility. Together, these results provide the first empirical characterization of the recessions that occurred in the state in the last 20 years as well as a comparison with the national context.